PENGARUH LINGKUNGAN KELUARGA DAN EFIKASI DIRI TERHADAP MINAT MENJADI GURU PADA MAHASISWA JURUSAN PENDIDIKAN AGAMA ISLAM UNIVERSITAS ISLAM MALANG - Lailatul Fikriyah; Ika Ratih Sulistiani; Dian Mohammad Hakim (VICRATINA, 2021)
Interest in bsecoming a teacher is a desire to become a teacher. However, not all student who majored in Islamic education only grounded by self wiliingness of its own, but there are many factors that can effect a person’s interest to become educators. Including family environment and self-efficacy. The purpose of this study was to determine the influence of the family environment and self-efficacy on the interest in becoming a teacher for students majoring in PAI, Islamic University of Malang. The analysis used in this study is multiple linear regression analysis, partial test (T) and simultaneous test (F). The results of the research that has been done declare that: (1) family environment had significant effect on the interent to be a teacher with a value tcount 2,480> ttable 1,97377. (2) self-efficacy had no significant effect on the interent to be a teacher with a value tcount 0,234> ttable 1,97377. (3) family environment and self-efficacy simultaneously had significant effect on the interent to be a teacher with a calculated Fcount og 3,448> Ftable 3,05. Keywords : Family Environment, Self-Efficacy, Interest to be a Teacher.